The Effect of Snowball Throwing Model on Students' Learning Outcomes in Pancasila Subject at Grade V of Taman Asuhan Pematangsiantar Elementary School - Okto Priadi Limbong; Radode Kristianto Simarmata; Bernard Simanjuntak (International journal of technology and education research, 2026)
This research is motivated by the low learning outcomes of students in the Pancasila Education subject in grade V of Taman Asuhan Pematangsiantar Elementary School. This problem is caused by the learning process that still uses conventional methods so that students are less active and less involved in learning activities. As a result, students' understanding of the Cultural Diversity material has not achieved the expected learning objectives. To overcome this problem, the Snowball Throwing learning model is applied which can increase student activity, interaction, and participation during the learning process. This study aims to determine the effect of the Snowball Throwing learning model on student learning outcomes in the Pancasila Education subject on Cultural Diversity in grade V of Taman Asuhan Pematangsiantar Elementary School. This study uses a quantitative approach with a Pre-Experimental Design and One Group Pretest-Posttest design. The research sample is 30 students. Data collection techniques are carried out through tests in the form of pretests and posttests. Research data are analyzed using normality tests and Paired Sample T-Test hypothesis tests. The results showed that the average pretest score for students was 36.67, with an increase in the posttest score to 86.53. Based on the hypothesis test results, the calculated t-value was -19.495 and the t-table value was -1.699 at a significance level of 0.05, with a 2-tailed significance value of 0.000 <0.05. Since the calculated t-value is > t-table, i.e., -19.495 > -1.699, H0 is rejected and Ha is accepted. This indicates a significant effect of the Snowball Throwing learning model on student learning outcomes.